Injury prevention program for juvenile soccer players: effects on physical performance, awareness of injury prevention measures and injury rates / Ahmed Fadhil Farhan - Farhan, Ahmed Fadhil (2015)
The purpose of this study was to investigate the effects of an injury prevention program (IPP) on physical performance, awareness of injury prevention measures and incidence of injury among junior male Malaysian soccer players. Participants (N=50, age=13.34±0.47 years, BMI=20.96±1.57 kg/m ) were assigned randomly into experimental (EXP, n=25) or control (CON, n=25) groups. The IPP consisted of exercise training (five times per week) and educational classes (three times per week) for 12 weeks. The CON group continued training as usual. Both groups performed a battery of soccer-specific physical tests at baseline, middle and after the intervention; 1) Standing long jump test (explosive leg power); 2) Sargent jump test (vertical jump height); 3) Illinois agility test (agility); 4) Prone hold test (core stability) and 5) 20m sprint test (running speed). A questionnaire containing 24 questions regarding awareness of injury prevention strategies and practices, as well as a measure of injury rates was administered at baseline and post-intervention. The incidence of injury was calculated using a formula: (incidence rate = number of injuries/hours of exposure) x 1000. At the end of the intervention, analysis using the repeated measures ANOVA showed the EXP group was significantly higher in explosive leg power (7.82% vs - 4.39%, p=0.01), vertical jump height (15.55% vs 5.12%, p=0.01), agility (-4.34% vs - 0.59%, p=0.01), core stability (48.25% vs 12.29%, p=0.01) and speed (-7.69% vs 1.64%, p=0.01), compared to CON. The independent /-test for comparisons on the awareness of injury prevention measures (strategies and practices), and rates of incidence injuries were significantly higher (p<0.05) in the EXP group than the CON group. The incidence rates per 1000 hours of practice and match were 10.93 in the EXP group and 13.17 in the CON group, which equates to 17% fewer injuries in the EXP group. The incidence rates post-test in EXP group was 4.26 and 1.19 for 1000 hours of practice time, and 12.01 per 1000 hours of match time, while CON group incidence rates post-test was 6.72, and 3.02 per 1000 hours of practice time and 16.09 per 1000 hours of match time, which equates to (36%, p<0.05) significantly decrease in overall injuries in the EXP group. In conclusions, these findings demonstrate that the IPP may be effective for improving soccer-specific physical performance and enhancing awareness of injury prevention measures that may in turn reduce the injury incidence.